A probabilistic approach for optimal power cable ampacity computation by considering uncertainty of parameters and economic constraints. (March 2019) - Shabani, Hamed; Vahidi, Behrooz
Highlights: A probabilistic method introduced for computation of power cable ampacity. Considering Uncertainty of affected parameters based on heuristic method. Economic aspects and minimize installation cost considered. Abstract: This study presents an algorithm to calculate the best ampacity of cable considering economic aspects and uncertainty of affected parameters based on heuristic optimization (ICA) method and probabilistic approach (Monte Carlo). The objective function of this algorithm includes cable arrangement and backfill dimensions considering uncertainty of parameters to maximize conformity of ampacity and load current and minimize installation cost. The two major factors affecting backfilling are dimensions of backfill envelop and substantial cost involved, and the other is the amount of cable ampacity to be increased by using the backfill according to load current profile. Furthermore, statistical variation of cable system parameters, such as fluctuation of load current, uncertainty of resistivity of native/backfill soil and ambient temperature are the most important factors to achieve the best configuration, optimum ampacity and related cost that are implemented in this paper by a novel optimization algorithm. However, since all of these parameters are random in nature, some of them vary along the cable route with the weather and seasons or age of the cable. Therefore, as shown in this paper, it is necessary to determine the ampacity at the design stage based on probabilistic approach, not on a deterministic basis.